The impact of an intensive care unit admission on the health status of relatives of intensive care survivors: A prospective cohort study in primary care. Issue 1 (31st December 2022) - Naaktgeboren, Rick; Zegers, Marieke; Peters, Marco; Akkermans, Reinier; Peters, Hans; van den Boogaard, Mark; van de Laar, Floris A.
Abstract: Background: Relatives of intensive care unit (ICU) survivors may suffer from various symptoms after ICU admittance of their relative, known as post-intensive care syndrome-family (PICS-F). Studies regarding PICS-F have been performed but its impact in primary care is unknown. Objectives: To explore health problems of relatives of ICU survivors in primary care. Methods: This is an exploratory prospective cohort study in which we combined data from two hospitals and a primary care research network in the Netherlands. ICU survivors who had been admitted between January 2005 and July 2017 were identified and matched by sex and age with up to four chronically ill (e.g. COPD, cardiovascular disease) patients. In both groups, relatives living in the same household were identified and included in this study. Primary outcome was the number of new episodes of care (International Classification of Primary Care-2) for up to five years. Hazard ratios (HRs) for the total number of new episodes were calculated. Results: Relatives of ICU survivors ( n  = 267, mean age 38.1 years, 41.0% male) had significantly more new care episodes compared to the reference group ( n  = 705, mean age 36.3 years, 41.1% male) 1–2 years (median 0.11 vs. 0.08, HR 1.26; 95% confidence interval (CI) 1.03–1.54) and 2–5 years (median 0.18 vs. 0.13, HR 1.28; 95%CI 1.06–1.56) after ICU discharge. No differences were found in the period before ICU admission. Conclusion: Relatives of ICU survivors present more morbidity in primary care than relatives of chronically ill patients up to five years after ICU discharge.